2001
DOI: 10.1007/s002640000191
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quadriceps femoris functional deficits following intramedullary nailing of isolated tibial fractures

Abstract: This retrospective study assessed 5 male and 5 female patients, age 35.1±16 years, height 171.8±12 cm, and weight 75.5±18 kg (mean±SD) who were more than 1 year post isolated tibial fracture (18±6 months) and had been treated with an intramedullary tibial nail. Subjects completed a 12-question visual analog scale, a physical symptom and activity of daily living survey, and were also tested for bilateral isokinetic (60°/s) quadriceps femoris and hamstring strength. Knee pain during activity, stiffness, swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Tibial nails should be positioned in a manner which minimises trauma to the extensor mechanism of the knee. 82 It has been suggested that pain causes reflex inhibition of quadriceps with subsequent atrophy and/or aplasia. 83 EMG studies have shown a modification of neuromuscular control of quadriceps in patients with anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…Tibial nails should be positioned in a manner which minimises trauma to the extensor mechanism of the knee. 82 It has been suggested that pain causes reflex inhibition of quadriceps with subsequent atrophy and/or aplasia. 83 EMG studies have shown a modification of neuromuscular control of quadriceps in patients with anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 They found clear differences in quadriceps morphology in the nailed and unnailed limb. 9 Patients who had anterior knee pain at final follow up had lower functional scores than those who never had knee pain or those whose knee pain has disappeared over time.…”
Section: Discussionmentioning
confidence: 90%
“…Between the 6-and 12-month follow-up, gait asymmetry become almost normalized. Knee and ankle pain, joint stiffness, degenerative joint disease, rotational malalignment, complications due to soft tissue injury and muscle weakness are commonly reported following a tibial shaft fracture [2,4,6,25,26] and may affect development in gait asymmetry.…”
Section: Discussionmentioning
confidence: 99%